System Design for Active Tremor Stabilization - Somisetti, Kiran; Jain, Charu; Chugh, Aarti; Charaya, Nisha (International Journal of Psychosocial Rehabilitation, 2020)
Parkinson’s disease, also known as tremors is one of the leading disability that is prevailing globally. Many people are affected by this disease. Generally, men are 1.5times more prone to suffer from tremors than women. According to scientists, this disease is partially curable by medications and also by complementary support therapies. But these have not resulted to be efficient in controlling tremors. Therefore scientists have developed many models to control the effects of tremors. Based on the previous studies, it was found that many inventions have been done to reduce the effects of vibrations but had few limitations. So, this paper exhibits the system that attains low cost and efficient device by using classic PID controller. This PID controller is tuned in such a way that it gives in best optimum result. The system design is done in Simulink software. This simulation study can be further used to develop a device.